Pengaruh Pembiayaan Mudharabah dan Musyarakah Terhadap Likuiditas Industri Bank Syariah di Indonesia - Ramadhani, Aulia; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aimed to know the influence of financing based on profit sharing againstÂ Islamic Banking Industry liquidity in Indonesia from January 2008 through June 2014. ThisÂ research used the quantitative approach method. The analysis technique used was multipleÂ linear regression and the equation was Y = 0,58 + 0,016 (PMUD) â 0,056 (PMUS)Based on the result of t-test, mudharabah financing and musyarakah financing partiallyÂ did not influence significantly to liquidity with t test result consecutively 0,765 forÂ mudharabah financing and 0,621 for musyarakah financing. The result of simultaneous testÂ showed that mudharabah financing and musyarakah had significant effect to IslamicÂ banking industry liquidity with siginificant value 0,000. And based on determination test result,Â the value of R Square is 0,593 or 59,3% that showed the ability of mudharabah financing andÂ musyarakah financing in explaining liquidity of 59,3% and the remaining 40,7% was explainedby other variables outside the model.